Evidence-based recommendations for delivering the diagnosis of X & Y chromosome multisomies in children, adolescents, and young adults: an integrative review - Kirsten A. Riggan; Kelly E. Ormond; Megan A. Allyse; Sharron Close (BMC, 2024)
Abstract Background The diagnosis of supernumerary X & Y chromosome variations has increased following the implementation of genetic testing in pediatric practice. Empirical evidence suggests that the delivery of the diagnosis has a lasting impact on how affected individuals and their parents perceive and adapt to the diagnosis. The purpose of this review is to synthesize the literature to obtain useful recommendations for delivering a pediatric diagnosis of a sex chromosome multisomy (SCM) based upon a growing body of quantitative and qualitative literature on patient experiences. Methods We conducted an integrative literature review using PubMed, Web of Science and CINAHL employing keywords "genetic diagnosis delivery," "genetic diagnosis disclosure," "sex chromosome aneuploidy," "Klinefelter syndrome" or ""47, XXY," "Jacob syndrome" or "47, XYY," "Trisomy X," "Triple X" or "47, XXX," and "48 XXYY from January 1, 2000, to October 31, 2023. Results Literature supports that patients and parents value the provision of up-to-date information and connection with supportive resources. Discussion of next steps of care, including relevant referrals, prevents perceptions of provider abandonment and commitment to ongoing support. Proactively addressing special concerns such as disclosing the diagnosis to their child, family, and community is also beneficial. Tables are provided for useful information resources, medical specialties that may be required to support patients, and common misconceptions that interfere with accurate information about the diagnosis. Conclusion Patient experiences suggest there should be heightened attention to diagnosis delivery, in reference to the broader ethical and social impacts of a SCM diagnosis. We present recommendations for optimal disclosure of a SCM diagnosis in early and late childhood, adolescence, and young adulthood.